Assessment of genotoxicity amongst smokers, alcoholics, and tobacco chewers of North India using micronucleus assay and urinary 8-hydroxyl−2′-deoxyguanosine, as biomarkers - Rana, S. V. S.; Verma, Yeshvandra; Singh, Gagan Deep (Environmental monitoring and assessment, 2017)
The main objective of the present study was to screen the genotoxicity caused by individual and combined habits of smoking, tobacco chewing, and alcohol consumption in human population of North India. Study recruited 67 male subjects aged 25 to 65 years. Buccal mucosal cells were subjected to micronucleus (MN) assay, and 8-hydroxyl-2-deoxyguanosine (8-OHdG) was estimated in their urine samples. Number and shape of the MN cells varied in the buccal epithelium of different groups. Maximum number of MN (0.47%) were found in tobacco chewers followed by smokers (0.45%) and alcoholics (0.44%) ( P < 0.05). These results reciprocated the concentration of urinary 8-OHdG. Maximum value for 8-OHdG was also recorded in tobacco chewers (21.07 ± 5.51 mg/mg creatinine) followed by smokers (20.25 ± 3.96 mg/mg creatinine) and alcoholics (19.06 ± 3.41 mg/mg creatinine) ( P < 0.05). Combined effects of these agents were found to be statistically different from individual effects. Carcinogenic compounds present in cigarette smoke, nitrosamines found in solid tobacco, and acetaldehyde, a metabolic product of alcohol, induce oxidative stress that manifests into genotoxicity. In conclusion, demographical differences occur in the genotoxicity caused by these three habits. MN assay and urinary 8-OHdG are simple, noninvasive, and reliable biomarkers of genotoxicity.